Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio are Predictors of Heart Failure - Durmus,Erdal (2015)
Abstract Background: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are inflammatory markers used as prognostic factors in various diseases. The aims of this study were to compare the PLR and the NLR of heart failure (HF) patients with those of age-sex matched controls, to evaluate the predictive value of those markers in detecting HF, and to demonstrate the effect of NLR and PLR on mortality in HF patients during follow-up. Methods: This study included 56 HF patients and 40 controls without HF. All subjects underwent transthoracic echocardiography to evaluate cardiac functions. The NLR and the PLR were calculated as the ratio of neutrophil count to lymphocyte count and as the ratio of platelet count to lymphocyte count, respectively. All HF patients were followed after their discharge from the hospital to evaluate mortality, cerebrovascular events, and re-hospitalization. Results: The NLR and the PLR of HF patients were significantly higher compared to those of the controls (p < 0.01). There was an inverse correlation between the NLR and the left ventricular ejection fraction of the study population (r: -0.409, p < 0.001). The best cut-off value of NLR to predict HF was 3.0, with 86.3% sensitivity and 77.5% specificity, and the best cut-off value of PLR to predict HF was 137.3, with 70% sensitivity and 60% specificity. Only NLR was an independent predictor of mortality in HF patients. A cut-off value of 5.1 for NLR can predict death in HF patients with 75% sensitivity and 62% specificity during a 12.8-month follow-up period on average. Conclusion: NLR and PLR were higher in HF patients than in age-sex matched controls. However, NLR and PLR were not sufficient to establish a diagnosis of HF. NLR can be used to predict mortality during the follow-up of HF patients.